THE PROS AND CONS OF ROUTINE CIRCUMCISION - Hovsepian, Deron (1951)
The origin of the practice of circumcision is an ancient one having a ritual significance in most cases, but the operation is done primarily for hygienic purposes amongst English-speaking people. Critical evaluation of the indication for circumcision suggests that the hygienic principles are probably overrated. If it were understood that the anatomy of the prepuce and glans has a morphological development which in most cases removes the possibility of phimosis after the third year, less emphasis would be placed on the necessity for the operation. On the other hand, the feeling exists that boys who will require circumcision because of phimosis, balanitis, etc., should not be subjected to the operation at the age when psychological trauma can result. Convention and conformity demand the continuation of the procedure in many areas. The decision to circumcise remains a matter of individual preference as prescribed in the doctor-patient relationship.